Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae), including new species and biological information - Cadena-Castañeda, Oscar J.; Weissman, David B. (Zootaxa, 2020)
We describe four new Glaphyrosoma species: G. brevivaginalis n. sp., G. huasteca n. sp., G. paragracile n. sp. and G. unumtympana n. sp. We redescribe and provide new distributional data for G. gracile, G. mexicanum and G. stephanosoltis. The subfamily status to tribe Glaphyrosomatini is proposed and a key to identify the genera is provided. The key to Glaphyrosoma species is updated to include the species here described. Finally, we present karyotype data and drumming information for selected species.